2021
DOI: 10.1177/02645505211041576
|View full text |Cite
|
Sign up to set email alerts
|

The stories of eight women managed by a community rehabilitation company during the Covid-19 pandemic

Abstract: This study explores the stories of eight women supervised by probation during the first national lockdown in the United Kingdom in response to the Covid-19 pandemic. Probation quickly implemented an exceptional delivery model to protect the health and safety of staff and service users. Covid-19 has highlighted societal disparities across the world, it can be suggested that this has hugely impacted the lives of women and further extending the gender inequality gap. Although acknowledging that this is a small-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…From the perspective of service users, a similar theme can be discerned. For example, in Woolford’s (2021) interviews with women under probation supervision in England and Wales, she found that the supervisory relationship was crucial to their well-being during the pandemic and was a source of support in relation to dealing with the pandemic as well as more practical matters. Participants also acknowledged that remote supervision was more difficult, and Woolford (2021) highlights the potential adverse impact on staff mental health and well-being.…”
Section: Remote Communication: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of service users, a similar theme can be discerned. For example, in Woolford’s (2021) interviews with women under probation supervision in England and Wales, she found that the supervisory relationship was crucial to their well-being during the pandemic and was a source of support in relation to dealing with the pandemic as well as more practical matters. Participants also acknowledged that remote supervision was more difficult, and Woolford (2021) highlights the potential adverse impact on staff mental health and well-being.…”
Section: Remote Communication: Strengths and Weaknessesmentioning
confidence: 99%
“…We might also think about this in relation to the perception that remote communication enables more open communication, because of the lack of judgement that people on probation might feel. It might be that remote communication is a tool with which to reduce the shame and stigma that people on probation experience when meeting with their probation officer (Woolford, 2021), suggesting another potentially productive way of integrating remote supervision with in person supervision in the future.…”
Section: Remote Communication: Strengths and Weaknessesmentioning
confidence: 99%
“…Data from early in the COVID-19 pandemic showed that this held true with 15% of women involved in the CL system stating that they did not trust any information on COVID-19 [25]. Furthermore, rules and regulations associated with probation, parole, and re-incarceration have constantly changed during the COVID-19 pandemic, as courts and probation and parole offices are intermittently closed and prisons and jails have attempted to lower admissions, producing an unpredictable environment, and much of community supervision has transitioned to remote settings [26]- [30].…”
Section: Introductionmentioning
confidence: 99%